EDUKASI PEMBERIAN MAKANAN PENDAMPING ASI ((MP-ASI DI TPA RAHMAH EL YUNUSIYYAH PADANG PANJANG - Cherysa, Cherysa; Laili Ramadani, Laili; Wahyuni, Sri Intan (PSGA LP2M IAIN Pontianak, 2024)
Complementary feeding is food and drink given to children 6-24 months to fulfill their nutritional needs. Proper provision of complementary foods is closely related to the knowledge of parents and adults around the child. The purpose of this study was to determine the education conducted by schools in providing complementary foods to children aged 6-24 months at TPA Rahmah El Yunusiyyah Padang Panjang. as well as the supporting and inhibiting factors of schools in conducting education on complementary feeding (MP-ASI) for children, which is accompanied by follow-up conducted by schools in the education of MP-ASI feeding at TPA Rahmah El Yunusiyyah Padang Panjang.The type of research that researchers use is qualitative research using a descriptive approach with data collection techniques, namely observation, interviews, and documentation. Data analysis techniques that researchers use are data collection, data reduction, data presentation and conclusion drawing or verification.Based on data analysis, it can be concluded that breastfeeding education (MP-ASI) at TPA Rahmah El Yunusiyyah Padang Panjang is carried out by; a) cooperation between schools and the Padang Panjang Health Office. b) the principal gives an explanation of MP-ASI education to loyal teachers on Saturday. c) explanation from teachers to parents about MP-ASI education. While the supporting factors in conducting MP-ASI education are the amount of free time given by schools to parents to provide direct exclusive breastfeeding and time to ask teachers about proper MP-ASI education for children and inhibiting factors for schools in conducting MP-ASI Feeding Education, namely the lack of manpower in managing MP-ASI at school.Keywords: Education, complementary food.